Socioeconomic differences between self- and interviewer-classification of color/race - Bastos, João Luiz; Peres, Marco Aurélio; Peres, Karen Glazer; Dumith, Samuel Carvalho; Gigante, Denise Petrucci (Revista de Saúde Pública, 2008)
OBJECTIVE: To assess (1) the consistency between self-classified and interviewer-classified color/race according to socioeconomic and demographic variables and (2) the magnitude of the ethnic-racial inequalities of income and socioeconomic status using self-classified and interviewer-classified color/race. METHODS: A cross-sectional population-based study was carried out among individuals of both sexes aged >;20 years (N=3,353), living in the urban area of a city in Southern Brazil, in 2005. A two-stage sampling scheme was adopted and data collection was performed at participants' homes. Face-to-face interviews were conducted using standardized precoded questionnaires. The consistency between self-classified and interviewer-classified color/race was checked by means of concordance proportions and kappa statistics. Ethnic-racial inequalities of income and socioeconomic status were estimated using linear and ordinal logistic regression models, adjusting for sex, age and schooling. RESULTS: The response rate was 93.5%. Despite the high reproducibility observed between self-classified and interviewer-classified color/race, a tendency towards whitening was seen among the interviewees. Self-classified brown (pardo) and black individuals were 1.4 and 1.5 times more likely to be classified as whites than as blacks and browns (pardos), respectively. Socioeconomically deprived strata presented higher kappa values. Ethnic-racial inequalities of income and socioeconomic status were found, and these were slightly greater using interviewer-classified color/race. CONCLUSIONS: Racial classification presents a tendency towards the whitening of participants by interviewers. Browns (pardos) and blacks were socioeconomically disadvantaged in comparison with whites.